Rationing of excessive demand on crowdinvesting-platforms - Oliver Mäschle (Universität Rostock, Institut für Volkswirtschaftslehre, 2012)
On crowdinvesting-platforms, non-publicly traded companies can offer equity to private investors. Currently, platforms like Crowdcube.com in Great Britain or Seedmatch.de in Germany are using a mechanism for the allocation of available shares best described by the phrase first come, first served. This paper argues that this kind of allocation of shares or rationing of excessive demand is not optimal. It describes the characteristics that rationing of excessive demand has to imply to protect the interests of involved parties in an appropriate manner. A recommendation for a concrete practical implementation is offered as well.
Keywords: D40; D45; G21; G32; L10; 330; crowdinvesting; market microstructure; rationing; equity; underpricing; excessive demand; Kapitalanlage; Social Web; Rationierung; Unternehmensgründung; Eigenkapital; Marktmikrostruktur